A variant on promoter of the cannabinoid receptor 1 gene (CNR1) moderates the effect of valence on working memory. Issue 2 (7th February 2018) - Fairfield, Beth; Mammarella, Nicola; Franzago, Marica; Di Domenico, Alberto; Stuppia, Liborio; Gatta, Valentina
ABSTRACT: Cannabinoid receptor 1 gene (CNR1) variants have been related to affective information processing and, in particular, to stress release. Here, we aimed to examine whether the endocannabinoid system via CNR1 signaling modulates affective working memory, the memory system that transiently maintains and manipulates emotionally charged material. We focused on rs2180619 (A > G) polymorphism and examined genotype data collected from 231 healthy females. Analyses showed how a general positivity bias in working memory (i.e., better memory for positive words) emerged as task strings lengthened only in carriers of the major allele (AA/AG). Differently, GG carriers showed better memory for affective items in general (i.e., positive and negative words). These findings are some of the first to directly highlight the role of variant on promoter of the CNR1 gene in affective working memory and to evidence a differentiation among CNR1 genotypes in terms of larger difficulties in disengaging from negative stimuli in GG carriers.